WOLONTARIUSZ NIEPEŁNOSPRAWNY – Z POTRZEBY WŁASNEJ CZY MYŚLENIA O INNYCH - Katarzyna Król (Studia Humanistyczne AGH, 2020)
“The most immutable and significant question of life is: What do you do for others?” (Martin Luther King Jr). This is the essence of volunteering, which involves conscious and selfless work for the community, it is showing help, but also a lesson in asking for it. The answer to this question is not easy, especially for a disabled person. The purpose of the article is to try to answer the question whether a disabled person can also be a donor of voluntary activities, and not just their recipient. Social participation, related volunteers is an attempt to answer the questions: what factors, procedures or mechanisms are behind undertaking social activity or lack of it, whether volunteering activity of disabled people is a desirable way out of the circle of excluded people.